(untitled) (Revista Argentina de Cirugía, 2025)
Hemorrhagic cholecystitis is a rare and serious complication of acute cholecystitis. The preoperative diagnosis is difficult. The few clinical cases reported in the literature suggest a strong association with anticoagulation therapy and high morbidity and mortality rates. We report two cases of hemorrhagic cholecystitis. The diagnosis was made intraoperatively in both cases and represented a challenge for on-call surgeons. The signs and symptoms are similar to those of acute cholecystitis, but the sudden onset of clinical impairment is a clear difference that could be misinterpreted as sepsis. Treatment requires urgent surgical intervention. Delays in diagnosis and surgery may result in significantly increased morbidity and mortality.